Analisis SWOT dalam Strategi Pemasaran Kredit PNS Silantap Sertifikasi pada PT BPR Kerta Raharja KCP Majalaya - Cindy Marina (Jurnal Dimamu, 2023)
Based on the results of observations and interviews, that the background of this research is very tight competition with other banks that have similar products. So that it causes customers to take over credit. This study aims to determine the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis in the marketing strategy of silantap certification civil servant credit products at PT BPR Kerta Raharja Majalaya Sub-Branch Office. The type of research used is descriptive qualitative, with PNS silantap Certification credit as the object of research. Primary data collection techniques through observation, interviews, literature study, and documentation. The results showed that there are 5 things that become strengths in the marketing strategy of PNS silantap certification credit products, there are 5 things that become weaknesses in the marketing strategy of certification silantap civil servant credit products, there are 3 things that become opportunities in the marketing strategy of silantap certification civil servant credit products, and there are 4 things that become threats in the marketing strategy of certification silantap civil servant credit products.